Jean y John Comaroff. Of Revelation and Revolution. Christianity, Colonialism and Conciousness in South Africa, vol. 1. Chicago: The University of Chicago Press, 1991. xx + 414 pp. - Saavedra Casco, José Arturo (Estudios de Asia y África, 1995)
-